2018
DOI: 10.1186/s40657-018-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation strata and human disturbance on bird diversity in green areas in a city in southern Chile

Abstract: Background: Urbanisation is a dominant geographical trend and an important component of global change, with unprecedented implications for socioeconomic , cultural and environmental characteristics. However, green areas, including original fragments, can help to conserve native diversity, improving the functioning of these artificial systems in the long term. Urban areas can still provide habitats usable by wild birds, however the structural characteristics of the habitat formed by different types of green are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 52 publications
1
9
1
2
Order By: Relevance
“…Abundant tree species and substantial maturity of vegetation vertical structure could supply food and habitats for more bird guilds (Canedoli, Manenti & Padoa-Schioppa, 2018). Some studies also have found a positive influence of canopy cover (Schuetz & Schulze, 2015; Threlfall et al, 2017), although shrub cover seems to be more important for both the alpha- (Newman et al, 2018) and beta-diversities (Munoz-Pedreros et al, 2018) of bird species. The deficiency in shrub cover within our study area was probably one of the major reasons for the poor state of the total avian community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant tree species and substantial maturity of vegetation vertical structure could supply food and habitats for more bird guilds (Canedoli, Manenti & Padoa-Schioppa, 2018). Some studies also have found a positive influence of canopy cover (Schuetz & Schulze, 2015; Threlfall et al, 2017), although shrub cover seems to be more important for both the alpha- (Newman et al, 2018) and beta-diversities (Munoz-Pedreros et al, 2018) of bird species. The deficiency in shrub cover within our study area was probably one of the major reasons for the poor state of the total avian community.…”
Section: Discussionmentioning
confidence: 99%
“…For example, most bird species positively respond to habitat area (Carbo-Ramirez & Zuria, 2011; Chaiyarat et al, 2019; Lepczyk et al, 2017), though the response may decrease when patch area reaches a threshold (Kim, Chae & Koo, 2007). Increased coverage of trees (Rega-Brodsky & Nilon, 2017), shrubs (Munoz-Pedreros et al, 2018), and vegetation structure heterogeneity due to different tree ages and large or multiple canopy layers (Franklin & Van, 2004; Lindenmayer, Franklin & Fischer, 2006) seem to be crucial for avian species richness (Chong et al, 2014; Lee & Rotenberry, 2015). The effect of shrubby and herbaceous species is probably exerted through the insect communities they sustain (Huang et al, 2015), which is consistent with the results of studies that have emphasized the importance of vegetative food resources (Chace & Walsh, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, environmental variables at the local scale are often more important than regional ones in determining species distribution and community composition in urban landscapes [38][39][40][41]. Such variables include patch level variables (e.g., green space size, amount of gray, tree, shrub and bare ground cover [6,26,35,42]), matrix level variables (e.g., distance from the city edge and center, building height [37,43,44]) and disturbance variables (e.g., anthropogenic noise, pedestrian and car traffic [45][46][47]).…”
Section: Introductionmentioning
confidence: 99%
“…The positions and numbers of vintage points were placed randomly in view of the size of the wetland. Waterbirds counts from all points were repeated at a regular interval of 7days and for each site, counting period lasted for 10 min to minimize the counting errors (Sarkar et al 2014, Muñoz-Pedreros et al 2018, Issa 2019. Birds were counted from each sighting point with a 25 m radius covering 360° arc (Hutto et al 1986, Issa 2019.…”
Section: Census Methodsmentioning
confidence: 99%